Synthesis and structural characterization of Ba14Pd3Ir8O33 - Burley, J; Battle, P; Jordan, N; Sloan, J; Weill, F (2003)
Ba14Pd3Ir8O33 has been prepared in polycrystalline form and characterized by X-ray, neutron and electron diffraction, lattice imaging and magnetometry. The structure can be described as the n=5,m=9 member of the (A3O9)n(A3A′O 6)m series which derives from the n=∞, m=0 2H perovskite structure. Ir and Pd cations occupy chains of octahedral and trigonal-prismatic sites in a disordered manner. An alternative description of the structure in (3+1)-dimensional superspace is also presented. No magnetic phase transitions were observed above 5K. © 2003 Elsevier Science (USA). All rights reserved.